The first family - Palmer, Michael, 1942-2013; Palmer, Daniel, 1962- (St. Martin's Press, 2018)
A doctor informs the President and First Lady that to make a diagnosis on their son Cam, they need to find other people with the same symptoms to conduct additional testing, but when two young people Dr. Lee has found, each with exceptional gifts, are murdered, Cam's condition suddenly takes on a terrifyingly new dimension. As Dr. Lee searches for answers, he will uncover unimaginable secrets and dark betrayals that breach the highest levels of security.
Keywords: Physicians -- Fiction; Medical fiction; Suspense fiction